Pemberdayaan masyarakat melalui kewirausahaan dan Green ECONOMY Desa Manunggal Kecamatan Labuhan Deli Kab. Deli Serdang - Surbakti, Syamsul Bahri; Daulay, Akman; Puspa, Sri; Yunanda; Sukarsih (Jurnal Derma Pengabdian Dosen Perguruan Tinggi (Jurnal DEPUTI), 2025)
The objective of the community service program is to empower the community of Manunggal Village, Labuhan Deli Sub-district, Deli Serdang Regency, through the promotion of a green economy-based entrepreneurship model. The program is designed to enhance community welfare by fostering the concept of environmentally sound entrepreneurship and promoting sustainable local economic development. The program is designed to equip entrepreneurs with the necessary skills and knowledge to incorporate green economy principles into their business practices. These principles encompass a wide range of practices, including waste management, organic crop cultivation, and the use of renewable energy sources.The program is structured to facilitate the development of practical business proposals, the creation of basic financial reports, and the integration of technology into business management.It is anticipated that the implementation of these activities will have a multifaceted impact on the community of Manunggal Village. Specifically, it is expected to enhance the community's capacity to manage sustainable independent businesses, increase income, and reduce unemployment. The program is designed to foster collective awareness regarding the significance of environmental protection through the implementation of responsible business practices.The implementation method of this service activity consists of presentations, lectures with question and answer sessions, and hands-on exercises.The final stage involves an evaluation phase, during which participants receive training on drafting practical business proposals.Following the conclusion of the service activity, a follow-up interview session was conducted to obtain feedback and evaluate the impact of the activity's implementation.